Dose effects of ultraviolet and terahertz laser radiation on the plasma membrane of erythrocytes - Sichevska, Larysa; Ovsyannikova, Tetiana; Zabelina, Iryna; Kovalenko, Alyna; Levchenko, Olexandr; Gurin, Oleg (Biophysical Bulletin, 2025)
Background: In modern medicine, various technical means and developments are actively used in invasive intravascular (IVL) and non-invasive transcutaneous blood irradiation methods, including low-intensity laser radiation (LLLR) of various ranges. Despite the positive clinical results of such exposure, the physical and molecular mechanisms remain incompletely understood. Ultraviolet (UV) and terahertz (THz) ranges of electromagnetic radiation are classified as biogenic; therefore, establishing their effects at the level of blood cells will allow them to be recommended for use in medical and biotechnological practice after the development of appropriate exposure methods.The objective was to study the biogenic activity of ultraviolet (UV) and terahertz (THz) ranges of LLLR on the structural and functional state of red blood cells of rats in vitro.Materials and methods: Using methods of microelectrophoresis, spectrophotometry and chemical erythrograms, the following was studied: zeta potential of red blood cells; the content of the primary products of lipid peroxidation in the red blood cells (fatty acid conjugates of membrane of red blood cells phospholipids — diene (DK), triene (TK), and tetraene (TTK), oxodiene (ODK); resistance of erythrocytes to the action of an acid hemolytic after previous laser irradiation in the UV and THz ranges. Laser irradiation of the samples in the UV range was carried out by a nitrogen pulsed laser (λ = 0.337 μm), with the average radiation power 5 mW; irradiation in the THz range with a continuous CO2 laser (λ = 118.8 μm), the average radiation power is 20 mW. When the samples were irradiated, the density of radiation power W did not exceed 7 W/m2. The exposure dose under nitrogen laser irradiation was D1UV=0.109 J/cm2, D2UV=0.327 J/cm2, D3UV=0.546 J/cm2. Under CO2 laser irradiation, the exposure dose was D1THz=0.624 J/cm2, D2THz=1.871 J/cm2, D3THz=3.119 J/cm2. The thickness of irradiated red blood cell suspension layer was 1 mm.Results: The effect of low-dose LLLR UV and THz radiation causes physicochemical changes in the plasma membrane of erythrocytes. A nonlinear dose-dependent decrease in the electrokinetic potential of the cell surface and an increase in the hemolytic sensitivity of erythrocytes against the background of activation of lipid peroxidation processes in erythrocyte membranes have been established.Conclusions: Under the influence of LLLR, the free-radical peroxidation of lipids of erythrocyte membranes is stimulated. Pronounced biogenic activity of UV of LLLR was detected at the level of erythrocyte membranes. The obtained data can be used to expand the spectrum of application of LLLR of the UV range in IVL techniques.